Value of medicinal use of the flora used by the people of Victor Larco, Trujillo, La Libertad, Peru - Mostacero-León, José (2020)
The demographic expansion worldwide, and in Peru, particularly brings with it a number of problems, highlighting among them, those related to health; being this, a fundamental pillar for the progress and development of the peoples; for this reason, the present investigation focused on determining the medicinal use value of the flora used by the inhabitants of the Víctor Larco district, Trujillo, La Libertad, Peru. A total of 96 semi-structured interviews were applied to the residents of the mentioned district, in order to obtain Information regarding the common name, part used, type of preparation, method of application, medicinal uses, as well as the in- dex of use value (IVU). In parallel, the specimens reported by the population were collected, dried, assembled, labeled and taxonomically determined. 50 species of plants for ethnome- dical use in the district are reported; Distributed in 46 genera and 30 families, of which they stand out for their number of species: Asteraceae (7), Lamiaceae (4), Fabaceae (3), Liliaceae (3) and Rutaceae (3). It is concluded that the most important species used in the treatment and / or cure of the diseases suffered by the population of the Victor Larco district, according to their Use Value Index (IVU) are: Linum usitatissimum L. “linaza”, Cymbopogon citratus (DC.) Stapf “hierba luisa”, Citrus limon (L.) Osbeck “limón”, Aloe vera (L.) Burm.f. “sábila”, Solanum tuberosum L. “papa”, Hordeum vulgare L. “cebada” y Morinda citrifolia L. “noni”